2003
DOI: 10.1007/s00018-003-2249-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein and its effect on human blood platelets

Abstract: Events leading to hyperactivity of human blood platelets are accompanied by an enhanced risk of atherosclerosis and arterial thrombosis. Lipoprotein disorders affect platelet functions, and hypersensitive platelets are observed in various stages of hyperlipidemia. Low-density lipoprotein (LDL), a circulating complex of lipids and proteins that is increased in hypercholesterolemia, enhances platelet function and increases sensitivity of platelets to several naturally occurring agonists. LDL sensitizes platelets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 104 publications
2
64
0
3
Order By: Relevance
“…[41][42][43] The activation process could potentially be mediated by VWF, since LDL has been shown to release VWF from EC. 44 46 Additionally, studies in LDLR Ϫ/Ϫ /VWF Ϫ/Ϫ mice demonstrated a reduction in atherosclerotic lesion development in regions of the aorta exposed to turbulent flow.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] The activation process could potentially be mediated by VWF, since LDL has been shown to release VWF from EC. 44 46 Additionally, studies in LDLR Ϫ/Ϫ /VWF Ϫ/Ϫ mice demonstrated a reduction in atherosclerotic lesion development in regions of the aorta exposed to turbulent flow.…”
Section: Discussionmentioning
confidence: 99%
“…LDL enhances platelet function and increases sensitivity of platelets to several naturally occurring agonists. LDL sensitizes platelets via binding of apolipoprotein B-100 to a receptor on the platelet membrane and via transfer of lipids to the platelet membrane [22]. Thus, increased platelet susceptibility to several agonists may enhance the risk of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Several LDL and oxidized LDL receptors may function as signal-transduction receptors, and CD36 (GPIV) is a more likely candidate. 24,25,27 The ability of fatty acid-free albumin and indomethacin to block partially HOCl-LDL-induced aggregation, also suggests a role for lipid mediators, 61,77,78 whereas partial sensitivity to indomethacin indicates that PLA 2 activation and TxA 2 are not essential for HOCl-LDL stimulation of platelet function. These results suggest that several mechanisms exist which involve both initial activation pathways as well as events required for the stabilization of platelet aggregates.…”
Section: Platelet Aggregation Bymentioning
confidence: 99%
“…18,19 Cell-associated lipoxygenase is also implicated in LDL oxidation by formation of reactive aldehydes. 2 n-LDL itself can potentiate platelet function, [20][21][22][23][24] complicating analyses of the roles of n-LDL versus ox-LDL in the pathogenesis of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%